Depositional environmental change of the Kathmandu Valley sediments inferred from the stratigraphy, sedimentological and mineralogical study - Paudel, MR; Sakai, H (Journal of Nepal Geological Society, 2008)
Thick sandy and gravelly sequences were recognised between the central and southern part of the Kathmandu Basin, which is named as Sunakothi Formation (Fm). We designated the type locality of the formation at Sunakothi, 3.0 km to the south of Patan (Paudel and Sakai 2005). This formation is extensively distributed in the Nakkhu, Kodku and Godawari Khola ranging in altitude from 1420 m in the southern margin (at Jorkhu) to 1300 m in the central part. The average thickness of this formation is 45 m. The sedimentary strata are gently inclined toward the north. On the basis of geological mapping this formation is located between muddy part of the Kalimati Formation of the ancient Kathmandu Lake, and covered by terrace gravel deposits, and divided into the following four stratigraphic units: (1) muddy rhythmic basal part, (2) sandy lower part, (3) muddy, sandy and gravelly middle part, and (4) laminated silty upper part. Basal part shows transitional from lacustrine to fluvial environment in the south and prodeltaic toward the basin center. Lower part shows sandy fluvial to lacustrine delta front, middle part shows sand bar, muddy floodplain and gravelly channel–fill deposits. Upper part of this formation is restricted only in the southern part of the basin, and shows marginal shallow lacustrine environments. In order to clarify the causes of change from open lacustrine facies of the Kalimati to Sunakothi Formation, whether this change has tectonic or climatic origin, we examined sedimentary facies change and mineralogical study of this Fm, overlying and underlying Formation. Both sedimentological and mineralogical study of this formations indicate that sediments of the Sunakothi Formation which have hidden history of the draining of the Paleo-Kathmandu lake, indicates that sediments of this formation were deposited at the time of lake level rise and fell. The causes of this change are due to the late Pleistocene climatic change (seasonal and prolonged dry climate indicated by smectite, and precipitation of calcite mineral at the basal part of the Sunakothi Formation) of the Katmandu Valley and triggering of the basin margin tectonics. Thick gravel sequence in the southern margin is the alluvial fan before the origin of the ancient lake, while thick gravelly facies located above the Sunakothi Formation deposited during the Late Pleistocene age. REFERENCE Paudel, M. and Sakai, H., 2005, Depositional environments and stratigraphic position of the Sunakothi Formation in the southern part of the Kathmandu Valley, Central Nepal, Abstract, the 112th Annual Meeting of the Geol. Soc. Japan, pp. 339. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.6